2017
DOI: 10.1111/anu.12581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of complete fish meal replacement by rice protein concentrate with or without lysine supplement on growth performance, muscle development and flesh quality of blunt snout bream (Megalobrama amblycephala )

Abstract: An 8-week feeding trial was conducted to evaluate the effects of fish meal (FM) replacement by rice protein concentrate (RPC) with supplementation of microcapsule lysine (ML) or crystalline lysine (CL) on growth performance, muscle development and flesh quality of blunt snout bream. Four isonitrogenous and isoenergetic diets were formulated, including FM diet (containing 50 g/kg FM), RPC diet (FM replaced by RPC), MRPC diet (FM replaced by RPC with ML supplementation) and CRPC diet (FM replaced by RPC with CL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 47 publications
4
21
0
Order By: Relevance
“…Whole body moisture, protein, lipid and ash were not affected by dietary treatments indicating that the use of plant protein mixture in the diet (extruded feed) for blunt snout bream instead of FM had no negative impact on whole body composition, which confirms that FM could be replaced by plant protein mixture with EAA supplementation in the diet of this fish species. These findings are in agreement with the data obtained by Cai et al (), when FM was replaced by rice protein concentrate with supplemental EAA and those reported by (Zhou, Habte‐Tsion, Ge, Liu, et al, ; Zhou, Habte‐Tsion, Ge, Xie, et al, ) when FM was substituted by canola meal and cottonseed meal respectively in the diet of the target species.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Whole body moisture, protein, lipid and ash were not affected by dietary treatments indicating that the use of plant protein mixture in the diet (extruded feed) for blunt snout bream instead of FM had no negative impact on whole body composition, which confirms that FM could be replaced by plant protein mixture with EAA supplementation in the diet of this fish species. These findings are in agreement with the data obtained by Cai et al (), when FM was replaced by rice protein concentrate with supplemental EAA and those reported by (Zhou, Habte‐Tsion, Ge, Liu, et al, ; Zhou, Habte‐Tsion, Ge, Xie, et al, ) when FM was substituted by canola meal and cottonseed meal respectively in the diet of the target species.…”
Section: Discussionsupporting
confidence: 93%
“…These findings indicated clearly the potential and profitable effect of EAA addition to complete a deficiency of EAA in PP when it comes to substituting FM even up to the total replacement (0 g/kg FM) in the diet for blunt snout bream. A similar study was carried out by Cai et al () who reported substitution of FM by rice protein concentrate with lysine supplementation had no adverse impact on growth performance, muscle development and flesh quality of the target species, which supports our results. Meanwhile, partial replacement of FM by canola meal (up to 75 g/kg FM) and cottonseed meal (112.5 g/kg FM) with supplemental methionine and lysine in the diet for the same species was reported by (Zhou, Habte‐Tsion, Ge, Liu, et al, ; Zhou, Habte‐Tsion, Ge, Xie, et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The shortage and rising cost of commercial fish meal has prompted researchers to investigate the production of cost effective feed formulations for cultured fish species [6,7]. Several plant protein sources/agricultural by-products have been tested as replacement for fish meal in fish diets [8][9][10][11][12][13][14] with a view to achieve cost reduction in fish production. However, studies with passion fruit seed cake are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, recent studies have been carried out to grasp the specific nutrient requirements on dietary carbohydrate (Zhou, Liu, Ge, Xie, & Xu, ), protein (Habte‐Tsion et al, ), AA such as methionine (Liang et al, ), threonine (Habte‐Tsion, Liu, et al, ), arginine (Ren et al, ), and histidine (Wilson‐Arop et al, ). In commercial situation, 6%–8% fishmeal is generally added in the diet, however, few studies dealt with the issue of fishmeal substitution by PP in the diet such as rice protein concentrate, and cottonseed meal (Cai et al, ; Zhou, Habte‐Tsion, Ge, Liu, et al, ). Meanwhile, the mechanism by which supplemental EAA collaborate to balance EAA profile when FM reduced to the low level in the diet of blunt snout bream still not clear and needs to be investigated.…”
Section: Introductionmentioning
confidence: 99%